Ekonomiczny, społeczny i egzystencjalny wymiar funkcjonowania placówek hospicyjnych i wolontariatu hospicyjnego - Rutkowska, Anna (Annales. Etyka w Życiu Gospodarczym, 2013)
The functioning of hospice institutions may be considered based on three fundamental, functions accomplished by it, i.e. existential, social and economic ones. Holistic evaluation of hospice care requires taking into account actual and potential advantages, possible to achieve both through society represented by all citizens, and through the economy.The article has a survey character – the literature is based on critical analysis within the scope ofthe subject raised. The work was made rich from two-year own experience of volunteer work. For the purpose of realization of the subject raised, empirical examinations were also conducted based on the method of shadow prices and logical matrix.In this paper, the implementation of the function of an existential volunteer hospice is considered on the basis of its ability to alleviate the suffering of patients’ mental and spiritual capacity and give them practical help by volunteers. The usefulness of hospices, which is a part of their social function, was studied by considering the point of existence and functioning of palliative and long-term care centres. In order to define the economic function of a voluntary service, micro and macroeconomic types of analysis were used. One should, however, emphasise that these examinations should have an interdisciplinary character.